Learning Interest and Spiritual Intelligence in Sharia Accounting Learning Outcomes: Minat Belajar dan Kecerdasan Spiritual dalam Hasil Belajar Akuntansi Syariah - Dioventa, Ambar; Nirwana, Nihlatul Qudus Sukma (Indonesian Journal of Law and Economics Review, 2024)
Background: Educational factors such as learning interest and spiritual intelligence are vital for academic performance. Specific Background: Understanding their impact within sharia accounting courses is crucial for improving student outcomes. Knowledge Gap: Few studies have examined the interplay of learning interest, spiritual intelligence, and motivation in this specific context. Aims: This research investigates the relationships among these factors and their effects on learning outcomes in sharia accounting courses. Results: A quantitative analysis involving 152 undergraduate accounting students revealed that both learning interest and spiritual intelligence positively influence learning outcomes. Furthermore, motivation moderates these relationships effectively. Novelty: This study offers new insights into how psychological factors interact to affect student performance in sharia accounting. Implications: Findings indicate that enhancing learning interest and spiritual intelligence can improve educational outcomes, with motivation as a critical moderator, thus guiding educators in developing effective teaching strategies. Highlights : Learning interest significantly enhances academic performance in sharia accounting. Spiritual intelligence contributes positively to learning outcomes in the course. Motivation serves as a crucial moderator between learning factors and student success. Keywords: Learning Interest, Spiritual Intelligence, Learning Outcomes, Motivation, Sharia Accounting